Maturation of Human Pluripotent Stem Cell-Derived Cerebellar Neurons in the Absence of Co-culture - Silva, Teresa P.; Bekman, Evguenia P.; Fernandes, Tiago G.; Vaz, Sandra H.; Rodrigues, Carlos A. V.; Diogo, Maria Margarida; Cabral, Joaquim M. S.; Carmo-Fonseca, Maria (Frontiers in Bioengineering and Biotechnology, 2020)
The cerebellum plays a critical role in all vertebrates, and many neurological disorders are associated with cerebellum dysfunction. A major limitation in cerebellar research has been the lack of adequate disease models. As an alternative to animal models, cerebellar neurons differentiated from pluripotent stem cells have been used. However, previous studies only produced limited amounts of Purkinje cells. Moreover, in vitro generation of Purkinje cells required co-culture systems, which may introduce unknown components to the system. Here we describe a novel differentiation strategy that uses defined medium to generate Purkinje cells, granule cells, interneurons, and deep cerebellar nuclei projection neurons, that self-formed and differentiated into electrically active cells. Using a defined basal medium optimized for neuronal cell culture, we successfully promoted the differentiation of cerebellar precursors without the need for co-culturing. We anticipate that our findings may help developing better models for the study of cerebellar dysfunctions, while providing an advance toward the development of autologous replacement strategies for treating cerebellar degenerative diseases.